1975
DOI: 10.1111/j.1600-0773.1975.tb00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Sodium, Potassium and Lithium in the Brain of Lithium‐treated Rats

Abstract: The distribution of lithium, and the effect of lithium on sodium and potassium in various parts of the rat brain were investigated. For this purpose a technique was developed by which the rat brain could be dissected in reproducible anatomical brain parts. Lithium was distributed unequally in the various brain parts. The concentration in hemispheres, cerebellum, thalamus and grey matter from the hemispheres was at the serum level, i. e. about 0.5 meq./kg of fresh tissue. The concentration in the hypothalamus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…The brains from control rats and rats treated with lithium for 50 days were divided longitudinally along the midline, one half being dissected into anatomical parts as previously described (EDELFORS 1975). The wet weight of the different brain parts was determined and the brain parts were vacuum freezed until constant weight was attained.…”
Section: Water Content and Water Binding Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The brains from control rats and rats treated with lithium for 50 days were divided longitudinally along the midline, one half being dissected into anatomical parts as previously described (EDELFORS 1975). The wet weight of the different brain parts was determined and the brain parts were vacuum freezed until constant weight was attained.…”
Section: Water Content and Water Binding Abilitymentioning
confidence: 99%
“…The brains from control rats and rats treated with lithium for 50 and 80 days, respectively were dissected as previously described (EDELFORS 1975) except that the thalamus and hypothalamus were pooled, while the cerebellum and pons were kept separate. The tissue samples were homogenized in 20 vol.…”
Section: Glycosaminoglycanes (Acid Mucopolysaccharides)mentioning
confidence: 99%
“…They found greater dif-ferences between the other areas than is evident in the present work. The levels in the hypothalamus are slightly higher than those of cerebellum and cortex but the difference is not as marked as that described by Edelfors (1975). However, the concentration of lithium in the nucleus accumbens, a non-striatal dopamine system, is not significantly different from the remainder of the cortex, suggesting that the concentration of lithium is not specific to dopamine systems.…”
Section: Discussionmentioning
confidence: 49%
“…The findings were similar to those of Ebadi et al (1974) who also found a high concentration of lithium in striatum following the acute administration of lithium to rats. Edelfors (1975) in a 3-5 week study of rats receiving lithium in diet found a significant decrease in the sodium concentration of the hypothalamus associated with an increase in lithium in the same area. While these studies appear to demonstrate conclusively that lithium is not distributed equally throughout brain but appears to be preferentially accumulated in striatum and brain stem, it remains uncertain whether this concentration is associated with the large number of nerve endings in these areas or if it is accounted for by uptake into a specific transmitter system.…”
mentioning
confidence: 96%
“…bled by heart puncture and decapitated. The brain was removed and dissected into hemispheres, cerebellum, pons, thalamus+ hypothalamus (Edelfors 1975).…”
Section: Methodsmentioning
confidence: 99%